PERBANDINGAN EFEKTIFITAS PIJAT OKSITOSIN TERHADAP INVOLUSI UTERI DAN PRODUKSI ASI PADA IBU POST PARTUM DI KABUPATEN KENDAL - Sri Rahayu; Desi Wijayanti Eko Dewi (Jurnal Ilmu Keperawatan dan Kebidanan, 2018)
Abstract                Various efforts have been made to reduce maternal mortality, one of them in Central Java Province with the program of counseling of pregnant mother (continuty of care / CoC model). The oxytocin hormone can cause uterine contractions and help the production of breast milk. So that oxytocin massage is one effort to reduce mother and baby mortality rate. The purpose of this study was to determine the effectiveness of oxytocin massage to uterine involution and breast milk production in post partum mother. This study used quasi experimental method with 48 postpartum mothers given treatment and 48 post partum mothers as control.In the uterine involution  48 (100%) of the respondents were not massaged or massaged in the third visit but in the first and second visits there was a slight difference of 1 (2.1%) of respondents. While in breast milk production there were 48 respondents (100%) who performed massage on the third visit but at first and second visit only slight difference between intervention and not given intervention proved by weight gain of baby from birth weight 2 (4.2%), research this is not in line with the purpose because results that the Pvelue obtained on the involution of 0.500 utility and the production of milk Pvelue 0.142 even on the third visit can not be obtained because the Pvluenya on the case and control no difference. It was concluded that oxytocin massage was more effective in breast milk production but not in uterine involution because there was still an increase in the weight of breastfed babies.Keywords: Okytocin Massage, uterine involution, milk production, post partum mother